Sustainable Urban Drainage Solutions and their Connection with the SDGs of the 2030 Agenda - Ramos, André dos Santos; Nascimento, Ana Paula Branco do (Technical and Scientific Journal Green Cities, 2025)
Objective – To investigate how sustainable urban drainage is articulated with the Sustainable Development Goals (SDGs) of the 2030 Agenda, mapping the relevance attributed to the targets in scientific articles. Methodology – Integrative review of 69 articles indexed in the Scopus database (“Urban Drainage” AND SUST*), selected between 2016 and 2025. The analysis combined quantitative approaches (temporal distribution, journals and countries) and qualitative approaches (methods, challenges and trends), enabling the identification of SDG frequency and relevance. Relevance – This study goes beyond merely identifying SDGs related to the theme by mapping the intensity of the connection (high, medium or low relevance) of each target with sustainable urban drainage, offering a systemic perspective rarely explored in national literature. Results – SDG 11 (Sustainable Cities and Communities), SDG 6 (Clean Water and Sanitation) and SDG 13 (Climate Action) were the most frequently mentioned, reflecting a focus on urban resilience and risk mitigation. SDGs 3 and 12 appeared with medium relevance, while specific social and climate targets (1.5, 13.2) remain underexplored. Theoretical/Methodological Contributions – Expands the understanding of sustainable urban drainage as a cross-cutting strategy for the SDGs, consolidating a perspective that integrates green infrastructure, socio-environmental justice and climate resilience. Provides a review protocol applicable to other 2030 Agenda themes. Social and Environmental Contributions – Demonstrates that sustainable drainage solutions reduce flooding, preserve water resources and increase urban biodiversity, while improving infrastructure in vulnerable areas, aligning mainly with SDGs 6, 11 and 13.